Joseph Jacquemotte : een levensbeeld - Demany, Fernand; Lahaut, Julien (Brussel : Het Volk, 1946)
Archief Bert Van Hoorick
Bibliotheek François Vercammen
Nederlands
Monografie
Keywords: Kommunistische Partij van België (KPB).; Jacquemotte, Joseph